PENGARUH PENGGUNAAN MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA KELAS 3 SD NEGERI DAWUNG 1 TAHUN PELAJARAN 2024/2025 - Savina Siti Nur Halimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine empirical answers about the effect of using snakes and ladders media on the mathematics learning outcomes of 3rd grade students of SD Negeri Dawung 1. In this study, researchers used an experimental method with a pre-experimental type and a One Group Pretest-Posttest Design. The population used in the study were all grade 3 students with a total of 20 students. The instrument used by researchers was in the form of multiple choice questions with a total of 20 questions, namely pre-test and post-test questions. Data collection techniques: 1) Test, 2) Documentation. The data analysis technique in this study used descriptive data analysis techniques and hypothesis analysis using the paired sample t-test formula. The results showed that: 1) Snakes and ladders media as learning media is designed in accordance with the development and characteristics of students so that it can motivate grade 3 students in understanding fraction material in mathematics subjects can be seen from the scores obtained by students who were previously in the low category after using learning media can be in the high category, 2). Snakes and ladders learning media is very influential on student learning outcomes, it can be seen from student learning outcomes in pre-test and post-test scores.